THE PEOPLE PERCEPTION ON BISNIS OF FISH CULTIVATION IN CAGES IN THE TERATAK BULUH VILLAGE SIAK HULU SUBDISTRICT,KAMPAR,REGENCY OF RIAU PROVINCE - Cesilia, Lisa; ', Kusai; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This Study was conducted in February 2017,located in The Teratak Buluh village subdistrict Siak Hulu District Kampar Riau Province, The purpose of this study was determine the people perception of fish Farming in cages and determine the people perception of fish farming in cages and determine the people perception of enchancement in come of fish farming in cages.Methods used in research is survey method. The determination of the respondents was connducted by census of 17 people. Analysis of the data used are descriptive analysis.The results of the study explained that the perception of the community on the waters in the Teratak Buluh village that the potential of village waters in good condition for business development. Based on the analysis of the 60% of people assessed well that the potential of waater in The Teratak Buluh village for the development of aquaqulture business. People’s perception on fish cultivation in cages 60% have good/positive perception.Based on the perception,the potential of waters in the village of Teratak Buluh supports the development of fish cultivation business in cages.Keywords:Perception,The people,Teratak Buluh